Characterization of the Shells in Layer-By-Layer Nanofunctionalized Particles: A Computational Study - Barchiesi, E.; Wareing, T.; Desmond, L.; Phan, A. N.; Gentile, P.; Pontrelli, G. (Frontiers in Bioengineering and Biotechnology, 2022)
Drug delivery carriers are considered an encouraging approach for the localized treatment of disease with minimum effect on the surrounding tissue. Particularly, layer-by-layer releasing particles have gained increasing interest for their ability to develop multi-functional systems able to control the release of one or more therapeutical drugs and biomolecules. Although experimental methods can offer the opportunity to establish cause and effect relationships, the data collection can be excessively expensive or/and time consuming. For a better understanding of the impact of different design conditions on the drug-kinetics and release profile, properly designed mathematical models can be greatly beneficial. In this work, we develop a continuum-scale mathematical model to evaluate the transport and release of a drug from a microparticle based on an inner core covered by a polymeric shell. The present mathematical model includes the dissolution and diffusion of the drug, and accounts for a mechanism that takes in consideration the drug biomolecules entrapped into the polymeric shell. We test a sensitivity analysis to evaluate the influence of changing the model conditions on the total system behaviour. To prove the effectiveness of this proposed model, we consider the specific application of antibacterial treatment and calibrate the model against the data of the release profile for an antibiotic drug, the metronidazole. The results of the numerical simulation show that ~85% of drug is released in 230 hours and its release is characterised by two regimes where the drug dissolves, diffuses, and travels the external shell layer at shorter time while the drug is released from the shell to the surrounding medium at longer time. Within the sensitivity analysis, the outer layer diffusivity is more significant than the value of diffusivity in the core, and the increase of the dissolution parameters causes an initial burst release of the drug. Finally, changing the shape of the particle to an ellipse produces an increased percentage of drug released with unchanged release time.